PENGUSAHAAN NIPAH DAN PERMASALAHANNYA - Djaban Tinambunan (Jurnal Penelitian Hasil Hutan, 1992)
A general   investigation  of thatch  palm  utilization  in South  Sumatra,  Lampung   and  West  Kalimantan  had  been  conducted  in  1991. The resuti  and  the  very  limited  publications available  show  that  the accurate  area,   distriburion  and potential  of thatch  palm  forests in Indonesia  are  not known yet.                 The traditional use  of  thatch  palm   leaves  for  making roof  has  been  know  for   a long  time  but  it is still  without any  improvement. while the utilization of the palm for  various commercial   products   is new  and,  therefore,   many  of its aspects  have  not  been  known  yet. It  is now realized   that  all of the palm  portions   such. as   leaf,  stem,  fruit   and juice   can  be used for   certain  products  with relatively high economical   values.lt  is noticed   that  in business   of thatch  palm   utilization   industry  in Indonesia,   several   constraisus   are  commonly  faced  such  as  the lack of data  of the palm   area, distribution and potential,   the  unclear  institution   responsible  for  the  commodity,    the  long procedure   of gelling  the permit for  managing  lhatch palm,   the difficult condition  of thatch palm field  and  lack of infrastructure, the lack of skilled labor,  technology,    environmental  information,  the  lack  of socio-   economical    analysis,  the  difficulty    in  getting  fund,  and the lack of real support from the government.Further   research  on   various  aspects   of  thatch  palm  utilization and development   are  necessary    in  order   to provide  scientific information  to  be  used  by interested   parties  so  that  the  rote  of the  commodity   in improving   the general  life  of  local  community  and increasing  government  earning   can  be realized.